The Crow - Croggon, Alison, 1962- (Cambridge, Mass. : Candlewick Press, 2007)
After a brief reunion with his lost sister Maered, who continues to pursue her dangerous destiny in the frozen North, orphaned Hem is sent south to Turbansk for safety but, as the armies of the Dark overrun the city, he flees with his mentor Saliman, his white crow Irc, and the orphan girl Zelika to join the resistance forces of the Light and finally learn his role in his sister's quest.
"Maps drawn by Niroot Puttapipat"--Copyright p.
Keywords: Supernatural -- Fiction; Magic -- Fiction; Orphans -- Fiction; Brothers and sisters -- Fiction; Fantasy; Science fiction; Self-realization -- Juvenile fiction